Eco-Friendly Design for Sustainable Gift Packaging - Andreja Pogačar; Diana Gregor-Svetec (Applied Sciences)
Modern packaging must be efficient, safe, and attractively designed, while also minimizing unnecessary waste. Eco-design principles, such as material reduction, reusability, and minimal environmental impact, were central to this study. We applied these principles to the development of innovative, multipurpose gift packaging and labels, optimizing material use, eliminating unnecessary printing, and integrating sustainable features such as a structural design which requires no gluing. Alongside choosing eco-friendly materials, namely corrugated cardboard and a biodegradable paper label, eco-design guidelines in packaging and label creation were followed. Packaging of unconventional shape without printing and different versions of labels for bottles and packaging were designed. Graphic elements included on the labels are the logo, illustration, 18th Century font, and lines of varying thicknesses. To provide additional information and enhance product appeal while reducing printing, an interactive element was incorporated. In the conducted study, the respondents of a survey and focus groups evaluated the quality, price range, and visual appeal of packaging and labels. For the augmented reality application, a label with a QR code was created. A scenario and a visual story board were created, and an animation activated via the QR code was produced. The usage experience was tested by the focus groups, who provided feedback on the animation and the overall experience. This iterative process ensured that the packaging and labels met both functional and experiential expectations.